A phase 2 trial of everolimus and pasireotide long-acting release in patients with metastatic uveal melanoma. Issue 3 (June 2016) - Shoushtari, Alexander N.; Ong, Leonard T.; Schoder, Heiko; Singh-Kandah, Shahnaz; Abbate, Kelly T.; Postow, Michael A.; Callahan, Margaret K.; Wolchok, Jedd; Chapman, Paul B.; Panageas, Katherine S.; Schwartz, Gary K.; Carvajal, Richard D.
Abstract : The aim of this study was to test the hypothesis that inhibiting mammalian target of rapamycin and insulin-like growth factor-1 receptor would be efficacious in metastatic uveal melanoma. This was a phase 2 trial of everolimus 10 mg daily plus pasireotide long-acting release 60 mg every 28 days enrolling patients with progressive, metastatic uveal melanoma to treatment until progression by Response Evaluation Criteria In Solid Tumors 1.1 (RECIST 1.1) or unacceptable toxicity. The primary endpoint was clinical benefit rate, defined as any objective response or RECIST 1.1 stable disease at 16 weeks. A subset of patients underwent baseline indium-111-octreotide scans. A total of 14 patients were enrolled, of which 13 were evaluable for the primary endpoint, before the study was terminated due to poor accrual. Three of 13 (26%) patients obtained clinical benefit. Seven of 13 (54%) had stable disease lasting for a median of 8 weeks (range: 8–16 weeks). Grade 3 adverse events deemed at least possibly related to study drugs were hyperglycemia ( n =7), oral mucositis ( n =2), diarrhea ( n =1), hypophosphatemia ( n =1), and anemia ( n =1). Seven of 14 (50%) patients required at least one dose reduction due to toxicity. Seven of eight (88%) patients with baseline indium-111-octreotide scans had at least one avid lesion, with significant intrapatient heterogeneity. There was a trend toward an association between octreotide avidity and cytostatic response to therapy ( P =0.078). The combination of everolimus and pasireotide has limited clinical benefit in this small metastatic uveal melanoma cohort. Dose reductions for side effects were common. Further investigation into the relationship between somatostatin receptor expression and cytostatic activity of somatostatin analogues is warranted.